Differences in the psychological preparedness of emergency nurses for caring for victims of violence against women according to nurse gender: a nationwide cross-sectional questionnaire survey in Japan - Akane Kato (Acute and Critical Care)
Background With the increasing incidence of violence against women (VAW), emergency department (ED) nurses should be trained to respond appropriately to victims of VAW (VVAW). However, the psychological preparedness of nurses caring for VVAW and its relationship to nurse gender remains unclear in Japan. Methods A nationwide self-administered questionnaire survey was conducted among 430 randomly selected certified emergency nurses. The questionnaire was a Japanese translation of the evaluation tools from the World Health Organization (WHO) curriculum "Caring for women subjected to violence: a WHO curriculum for training healthcare providers." Results The final sample included 104 participants, and the effective response rate was 24.2%. More than 60% of nurses had experience in caring for VVAW; however, only 10% had received training concerning VAW. The mean number of VVAW cared for by these nurses was 6.2 (standard deviation, 6.1) with no significant difference in nurse gender (P=0.52, effect size [ES]=0.09). Male nurses had a higher mean score of psychological preparedness than female nurses (22.6 vs. 20.4; P=0.03, ES=0.22); moreover, female nurses scored lower than male nurses on all items of the psychological preparedness evaluation. Less than half of the participants reported having institutional support systems. Conclusions Establishing an education program for all emergency nurses, providing support to ensure the psychological preparedness of female emergency nurses, and ensuring improvement of facilities nationwide are essential for enhancing nursing care for VVAW in Japanese EDs.